Genetic diversity, population structure, marker validation and kinship analysis for seedling stage cold tolerance in indica rice - Das, Sujata; Pandit, E; Nayak, D K; Tasleem, S; Barik, S R; Mohanty, D P; Mohanty, S P; Patra, B C; Pradhan, S K (ORYZA-An International Journal of Rice, 2018)
Cold stress affects rice production globally. In India, around 4 million hectares of rice area are affected by seedling stage cold stress. A panel of 48 indica rice genotypes including all phenotype classes viz. very highly tolerant to susceptible ones were analyzed with linked SSR markers for kinship, population structure and genetic diversity for seedling stage chilling stress tolerance. High level of genetic diversity existed in the panel population. The heterogeneity in the panel population favored the presence of linkage disequilibrium. The population structure could differentiate the panel into two sub-populations separating the tolerant and susceptible lines into separate sub-groups. A lower value of alpha (α=0.0589) indicated that the trait had a common primary ancestor. The three phenotypic groups i.e. susceptible, moderately tolerant and tolerant to very highly tolerant groups were clearly separated out by kinship and cluster analysis. The donor lines in the panel exhibited the presence of multiple QTLs as well as different QTL combination in different lines for the expression of tolerance to cold stress. These tolerant genotypes can be used as donor lines in breeding programs to incorporate different combination of cold stress tolerance QTLs. The molecular markers used in the study were observed to be robust one to identify the highly tolerant, moderately tolerant and susceptible genotypes. Hence, these markers will be useful for marker-assisted breeding programs.